Thermochemical Pretreatment of Lignocellulose Residues: Assessment of the Effect on Operational Conditions and Their Interactions on the Characteristics of Leachable Fraction - Contreras-Villacura, E (IWA PUBLISHING, 2015)
Annually, large amounts of agricultural residues are produced in Chile, which can be turned into a good opportunity to diversify the energy matrix. These residues have a slow hydrolysis stage during anaerobic digestion; therefore, the application of a pretreatment seems to be an alternative to improve the process. This work focused on applying a thermochemical pretreatment with NaOH on two lignocellulosic residues. The experiments were performed according to a 24 factorial design. The factors studied in a 24 factorial design were: temperature (60 and 120 degrees C), pretreatment time (10 and 30 minutes), NaOH dose (2 and 4%), and residue size (< 1 and 1-3 mm for wheat straw; 1-5 and 5-10 mm for corn stover). The analyzed response variables were the solubilization of organic matter, and the biodegradability of the lignocellulose hydrolysate. The statistical analysis of the data allowed the identification of the experimental conditions that maximized solubilization of organic matter and biodegradability. The main results showed that more aggressive experimental conditions could increase the breaking down of the structure; in addition, the time of pretreatment was not significant. Conversely, the less aggressive experimental conditions, regarding regent dosage and downsizing, favored the release of biodegradable organic matter. The main conclusion of this study was the identification of the operational conditions of the thermochemical pretreatment that promote maximum biogas production, which was caused due to the solubilization of a large amount of organic matter, but not because of the increase in biodegradability of the released organic matter.